Hukum Persaingan Usaha dan Dampak Terhadap Bisnis di Indonesia: Pengembangan UMKM (Usaha Mikro Kecil Menengah) Produksi D’jalan Coffe Solo - Aisyah, Shovi; Anggreini, Desvita; Uziella, Kiara (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Competition law enforcers in Indonesia have a crucial role in creating a healthy, fair, and competitive business climate. Especially for micro, small, and medium enterprises (MSMEs), MSMEs are started by individuals or small groups. This study aims to analyze the impact of the implementation of competition law on the development of MSMEs in Indonesia with a case study at D'jalan Coffe Solo, an MSME in the culinary and beverage sector. Through a qualitative descriptive approach, data were obtained from interviews, observations, and literature studies. The results of the study indicate that understanding and implementing the principles of competition law, such as the prohibition of monopolistic practices, unfair competition, and price collusion, can encourage MSMEs to grow sustainably and innovatively. D'jalan Coffe Solo shows that with a business strategy that prioritizes product differentiation, healthy cooperation, and compliance with regulations, MSMEs are able to compete healthily even amidst the dominance of large business actors. These findings recommend the need for broader socialization and assistance of competition law to MSME actors in order to create a fair and inclusive business ecosystem.